Lung Cancer Prognosis in Elderly Solid Organ Transplant Recipients. Issue 10 (October 2015) - Sigel, Keith; Veluswamy, Rajwanth; Krauskopf, Katherine; Mehrotra, Anita; Mhango, Grace; Sigel, Carlie; Wisnivesky, Juan
<x xml:space="preserve">Abstract</x> Background Treatment-related immunosuppression in organ transplant recipients has been linked to increased incidence and risk of progression for several malignancies. Using a population-based cancer cohort, we evaluated whether organ transplantation was associated with worse prognosis in elderly patients with non–small cell lung cancer (NSCLC). Methods Using the Surveillance, Epidemiology, and End Results Registry linked to Medicare claims, we identified 597 patients aged 65 years or older with NSCLC who had received organ transplants (kidney, liver, heart, or lung) before cancer diagnosis. These cases were compared to 114, 410 untransplanted NSCLC patients. We compared overall survival (OS) by transplant status using Kaplan-Meier methods and Cox regression. To account for an increased risk of non-lung cancer death (competing risks) in transplant recipients, we used conditional probability function (CPF) analyses. Multiple CPF regression was used to evaluate lung cancer prognosis in organ transplant recipients while adjusting for confounders. Results Transplant recipients presented with earlier stage lung cancer (P = 0.002) and were more likely to have squamous cell carcinoma (P = 0.02). Cox regression analyses showed that having received a non-lung organ transplant was associated with poorer OS (P < 0.05), whereas lung transplantation was associated with no difference in prognosis. After accounting for competing risks of death using CPF regression, no differences in cancer-specific survival were noted between non-lung transplant recipients and nontransplant patients. Conclusions Non-lung solid organ transplant recipients who developed NSCLC had worse OS than nontransplant recipients due to competing risks of death. Lung cancer-specific survival analyses suggest that NSCLC tumor behavior may be similar in these 2 groups.